2001
DOI: 10.1046/j.1365-2133.2001.04474.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopic eczema and the home environment

Abstract: Further research is needed to confirm these associations and additional research is needed to see whether they might be causative. Practical public health advice about the importance of controlling the home environment may then be targeted at families with atopic eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 30 publications
3
48
1
Order By: Relevance
“…The association between mold and AD was reported in previous studies. Several studies have reported a positive association between mold and AD [23,24,25,26]; another study in Germany suggested mold is not related with atopic eczema [27]. Sick building syndrome is a syndrome associated with an individual’s place of work or residence.…”
Section: Discussionmentioning
confidence: 99%
“…The association between mold and AD was reported in previous studies. Several studies have reported a positive association between mold and AD [23,24,25,26]; another study in Germany suggested mold is not related with atopic eczema [27]. Sick building syndrome is a syndrome associated with an individual’s place of work or residence.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors demonstrated to be associated with AD: personal factors (e.g., smoking habits, age, gender, nutritional status, number of siblings, lifestyle, allergy status, family history and occupation) [2] and indoor/outdoor environmental factors (e.g., house dust mite, animal dander, molds, cockroach infestation, occupational exposure, environmental tobacco smoke (ETS), air pollution, aeroallergens and climate) [3,4,5]. Many reports on indoor/outdoor environment in relation to AD were from Western populations [2,3,4,5,6] and little information on environmental risk factors associated with AD in Chinese children is available.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] However, there are few formal longitudinal studies that indicate how the home environment has changed over the past 50 years. We previously reviewed data regarding exposure to soap detergents, frequency of washing, and exposure to house dust mites.…”
mentioning
confidence: 99%